Efectos de la incorporación de abonos verdes en los suelos degradados del Ecuador. - Varas Mejía, Génesis Roberta (2023)
Green manures have positive factors in the soil, improving its physical, chemical and biological properties, especially in soils that are heavily compacted and eroded by conventional agriculture. The information obtained was detailed through the technique of analysis, synthesis and summary, with the objective of highlighting specific information on the effects of the incorporation of green manures in degraded soils in Ecuador. From the above detailed, it was determined that the most common causes affecting soil degradation are: deforestation, use of chemical products to fertilize cereal crops, climate change, heavy agricultural machinery, insufficient irrigation, overgrazing and depletion of soil organic matter. Green manures refer to the use of any plant in rotation, succession or combination of crops with crops incorporated into the soil or left on the surface as manure to preserve and improve their physical, chemical and biological properties. Legumes can be used as green manures, each of which is beneficial for increasing soil fertility and the productivity of related crops. Green manures can be used in various ways to improve degraded soils such as: green manure in association with annual crops, green manures associated with perennial crops, green manure with strips and/or mixture (legume mixture), green manure with perennial plants, green manure in crop rotation with annual crops and green manure as a cover crop. Plants used as green manure are beneficial for biological activity because they provide the soil with organic matter, which is a determining factor for microbial activity and provides a source of energy for microbial development